If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90(n + 18)(2n) = 180 Reorder the terms: 90(18 + n)(2n) = 180 Remove parenthesis around (2n) 90(18 + n) * 2n = 180 Reorder the terms for easier multiplication: 90 * 2n(18 + n) = 180 Multiply 90 * 2 180n(18 + n) = 180 (18 * 180n + n * 180n) = 180 (3240n + 180n2) = 180 Solving 3240n + 180n2 = 180 Solving for variable 'n'. Reorder the terms: -180 + 3240n + 180n2 = 180 + -180 Combine like terms: 180 + -180 = 0 -180 + 3240n + 180n2 = 0 Factor out the Greatest Common Factor (GCF), '180'. 180(-1 + 18n + n2) = 0 Ignore the factor 180.Subproblem 1
Set the factor '(-1 + 18n + n2)' equal to zero and attempt to solve: Simplifying -1 + 18n + n2 = 0 Solving -1 + 18n + n2 = 0 Begin completing the square. Move the constant term to the right: Add '1' to each side of the equation. -1 + 18n + 1 + n2 = 0 + 1 Reorder the terms: -1 + 1 + 18n + n2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 18n + n2 = 0 + 1 18n + n2 = 0 + 1 Combine like terms: 0 + 1 = 1 18n + n2 = 1 The n term is 18n. Take half its coefficient (9). Square it (81) and add it to both sides. Add '81' to each side of the equation. 18n + 81 + n2 = 1 + 81 Reorder the terms: 81 + 18n + n2 = 1 + 81 Combine like terms: 1 + 81 = 82 81 + 18n + n2 = 82 Factor a perfect square on the left side: (n + 9)(n + 9) = 82 Calculate the square root of the right side: 9.055385138 Break this problem into two subproblems by setting (n + 9) equal to 9.055385138 and -9.055385138.Subproblem 1
n + 9 = 9.055385138 Simplifying n + 9 = 9.055385138 Reorder the terms: 9 + n = 9.055385138 Solving 9 + n = 9.055385138 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + n = 9.055385138 + -9 Combine like terms: 9 + -9 = 0 0 + n = 9.055385138 + -9 n = 9.055385138 + -9 Combine like terms: 9.055385138 + -9 = 0.055385138 n = 0.055385138 Simplifying n = 0.055385138Subproblem 2
n + 9 = -9.055385138 Simplifying n + 9 = -9.055385138 Reorder the terms: 9 + n = -9.055385138 Solving 9 + n = -9.055385138 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + n = -9.055385138 + -9 Combine like terms: 9 + -9 = 0 0 + n = -9.055385138 + -9 n = -9.055385138 + -9 Combine like terms: -9.055385138 + -9 = -18.055385138 n = -18.055385138 Simplifying n = -18.055385138Solution
The solution to the problem is based on the solutions from the subproblems. n = {0.055385138, -18.055385138}Solution
n = {0.055385138, -18.055385138}
| 4+4v=24 | | 4w-4= | | 2x+6+3x=18+16 | | X(15x)=41 | | 190-w=288 | | 2(2x+4x)2= | | F(x)=5x^2-2x+7 | | 31=-9c-2c | | 15x+y=41 | | 84=5w-16 | | 2x+-17y=-13 | | Y+6=4(x-1) | | 9x-35=-x+5 | | 10-4(x-5)=2 | | 2+7=-2 | | 7x-12=3+6x | | y=78/X | | 4*(x+3)=12+4x | | 20x=25(x-1/5) | | X+15x=41 | | 27=-2+5(r-3) | | 5(8x-6)-3(-5x+4)= | | 26=5+4 | | -7(-8a+6)=17-3a | | 7t^2-1=8kt^2-2kt | | x^4-x^2+16x=0 | | -4x+5=-13x+39 | | 450=10+5 | | 2lne=c | | 5-1.5=6 | | y+4=4(x-1) | | 2((8x-6)+(-5x+4))= |